Przybliżone Obliczanie Częstości Skrętnych Drgań Własnych Pręta o Zmiennym Przekroju - Łączkowski, R. (Engineering Transactions, 1967)
The supports mentioned in the title are assumed to be elastic. The continuous bar is replaced model composed of many masses for which the matrix equation of natural vibration is derived: For various boundary conditions frequency equations are obtained the zeros determining the natural frequencies. A method for computing these frequencies as well as the corresponding relative torsion lines is described a computation scheme being also given for an electronic digital computer.The error of the matrix method is determined in function of the boundary conditions and the number of segments into which the bar has been divided. As an example the results of computation of natural torsional vibrations of a turbine blade, are confronted with experimental methods.